ZHÂHIRAH AL-MAZJI AL-LUGHAWÎ FÎ MUJTAMA’ DZAWÎ AL-USHÛL AL-‘ARABIYAH FÎ INDONESIA: KUNHAHÂ WA MABNÂHÂ WA DALÂLATUHÂ - Shehata, Islam Ragab; Mulyati, Yeti; Hadianto, Daris (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2021)
This article aims to discuss the phenomenon of code blending in society of Arab descent in Indonesia. By using ethnographic research methods, samples of data collected through direct personal interviews was analyzed. The results of the data analysis show that the phenomenon of code blending is rife in their conversations, something that is clearly visible in the mixing of Arabic with Indonesian. So that, they replace nouns with verbs, plural words with singular words, standard words with non-standard, and use the inflection Arabic for Indonesian and vice versa, so that the form and structure of the two languages are changed. This study also shows that this phenomenon is caused by a lack of mastery of Arabic and Indonesian by speakers, continuous communication in this way between families, because parents pass on Arabic and Indonesian vocabulary to their children and do not pass on their forms and structure of the sentence, or there is always the occurrence language contact in various situations such as schools and workplaces.